Mastering Autodesk Maya 2012 - Palamar, Todd (Autodesk official training guide., 2011)
"The exclusive, official guide to the very latest version of MayaGet extensive, hands-on, intermediate to advanced coverage of Autodesk Maya 2012, the top-selling 3D software on the market. If you already know Maya basics, this authoritative book takes you to the next level. From modeling, texturing, animation, and visual effects to high-level techniques for film, television, games, and more, this book provides professional-level Maya instruction. With pages of scenarios and examples from some of the leading professionals in the industry, author Todd Palamar will help you master the entire CG production pipeline. Provides professional-level instruction on Maya, the industry-leading 3D animation and effects software used in popular films, games, and commercials Covers the very latest Maya 2012 tools and features, including the new fluid simulation tools Showcases the techniques of professionals through numerous examples, demonstrating how to set up and manage 3D animation and visual effects pipelines Includes challenging tutorials and real-world scenarios from some of the leading professionals in the industry If you're looking for an in-depth, professional Maya resource to turn to again and again, this is the book you need"--